Darkwood - Breen, M. E. (New York : Bloomsbury, 2010)
A clever and fearless orphan endures increasing danger while trying to escape from greedy, lawless men and elude the terrifying "kinderstalks"--animals who steal children--before discovering her true destiny.
Reprint. Originally published: 2009.
Keywords: Adventure fiction; Orphans -- Fiction; Sisters -- Fiction; Wolves -- Fiction; Fantasy fiction